PELAKSANAAN KEBIJAKAN REKLAME DI KOTA PEKANBARU TAHUN 2006-2015 - Ditasman Ditasman (Universitas Riau, 2016)
Advertising Policy Implementation in Pekanbaru Year 2006-2015. This study aims todescribe the analysis of the implementation of the policy of billboards in the city of Pekanbaru. Asfor the issue of this research is to know how the policy deploy billboards in the city of Pekanbaruand anyone actors involved in the implementation of policies advertisement. The research problemis motivated by the Mayor passed regulations No. 24 of 2013 concerning the organization ofbillboards in the city of Pekanbaru. This causes a conflict of businessmen and community organizersbillboard advertisement rejecting the Mayor policy. The mayor’s policies have not been successfulin the process of policy Communication, Process Resource policies billboard, advertisement policydisposition process and Bureaucratic Structure advertisement policy, which did not go well. Thisstudy used qualitative methods. namely data obtained by interview, observation, documentationand then analyzed qualitatively The theory used was Edward III. The results showed that theimplementation of the policy of billboards in the city of Pekanbaru already implemented policyadministration billboards but the results have not been effective due to lack of attention to processCommunication policies, processes resource policies, processes disposis policies and structuresBureaucratic Policy billboards, Among the successful analysis of policy implementation billboardsby the Government Pekanbaru city not proved instrumental in the process Communication policies,processes resource policies, processes and policies disposition policies bureaucratic structure.